2013
DOI: 10.1309/ajcp66avbanvntqj
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Significance of Combined Hepatocellular-Cholangiocarcinoma With Stem Cell Subtype Components With Reference to the Expression of Putative Stem Cell Markers

Abstract: Objectives: To examine the clinicopathologic features of combined hepatocellular-cholangiocarcinoma (HC-CC), which the World Health Organization (WHO) proposed classifying into 2 types, and the expression of delta-likeSeveral markers and approaches have been used to detect and characterize hepatic stem/progenitor cells. [2][3][4][5] For example, the simultaneous immunohistochemical expression of an HCC marker (HepPar1 or a-fetoprotein [AFP]) and a biliary marker (cytokeratin [CK] 19 or carcinoembryonic antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 20 publications
3
41
2
Order By: Relevance
“…Previous reports showed that CHC with stem‐cell features including INT showed more malignant potential (i.e. worse prognosis and high proliferative activity) compared with HCC, and these findings are similar to the present study. Therefore, accurate diagnosis of INT is essential for clinical management.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports showed that CHC with stem‐cell features including INT showed more malignant potential (i.e. worse prognosis and high proliferative activity) compared with HCC, and these findings are similar to the present study. Therefore, accurate diagnosis of INT is essential for clinical management.…”
Section: Discussionsupporting
confidence: 93%
“…However, they provide valuable concepts for further elucidation of the pathogenesis of this diverse group of tumors. Interestingly, Ikeda et al [25] recently compared the survival rates of cHCC-CCs according to the amount of hepatic stem/progenitor cell-like components (<5 vs. >5% of the tumor area) and demonstrated that cHCC-CCs with ‘stem cell-like areas' occupying >5% of the tumor were associated with a poor survival. Therefore, it is possible that the presence and amount of tumor cells with stemness-like features within cHCC-CC are more important factors influencing prognosis than the various histological subtypes of cHCC-CC.…”
Section: Pathological Spectrum Of Primary Hepatic Carcinomas Expressimentioning
confidence: 99%
“…Previously, studies have shown that liver CSCs may contribute to the high rate of recurrence and the heterogeneity of HCC 3, 79 . Several studies have shown that a portion of HCCs express the progenitor cell phenotype, such as CK7 and CK19 10 . Actually, this portion of liver cancer has a significantly worse prognosis and a higher recurrence rate after treatment 11 .…”
Section: Introductionmentioning
confidence: 99%